P545 Safety of ustekinumab in pregnant patients with inflammatory bowel disease and in their offspring: results from the DUMBO registry of GETECCU. (21st January 2022) - Chaparro, M; Gutiérrez, A; Calviño-Suárez, C; Huguet, J M; Calvo, M; Aguas, M; Camargo Camero, R; de Jorge Turrión, M Á; Hervías Cruz, D; López Serrano, P; Marín Pedrosa, S; Martínez Montiel, P; et al.
Abstract: Background: The safety of ustekinumab in pregnant patients with inflammatory bowel disease (IBD) and in their offspring has been barely studied. Aims: Primary: To know the risk of serious adverse events (SAEs) in women exposed to ustekinumab during pregnancy and in their offspring. Secondary: To assess the risk of complications of the mothers and their offspring. To describe the patterns of use of ustekinumab during pregnancy in these patients Methods: Patients with IBD exposed to ustekinumab during pregnancy from DUMBO registry of GETECCU were included. DUMBO is a prospective, observational and multicentre registry, which enrols pregnant women with IBD over 5 years in 70 centres in Spain. The registry was kicked off in September 2019. SAE definition was based on "Clinical Safety Data Management: Definitions and Standards for Expedited Reporting by European Medicines Agency". Study protocol is summarized in figure 1. Results: 49 pregnant patients have been exposed to ustekinumab during pregnancy so far (table 1). All pregnancies were singleton. Two patients were lost of follow-up (1st and 2nd trimester) but had uneventful pregnancies up-to last visit. There were 2 miscarriages (4%) at 1st trimester of gestation, 34 newborns and 11 pregnancies that were still on-going at the time of this analysis. All patients were on ustekinumab at conception (57% of them 90 mg/8 weeks). A total of 12 patients (24%) withdrawn ustekinumab during pregnancy: 1 (8%) due to disease flare, 1 (8%) underwent surgery due to intestinal obstruction, 2 (17%) due to patient's choice (at 1st and 2nd trimester), and 8 (67%) due to clinicians' decision (1 at 1st, 5 at 2nd and 2 at 3rd trimesters). No patient flared up after ustekinumab discontinuation. 10 (20%) patients had SAEs: 2 miscarriages, 1 intestinal infection, 1 subcorionic hematoma, 3 preterm birth, 1 intestinal obstruction and perforation (underwent surgery), 1 preeclapmsia, and 1 stoma obstruction. A total of 34 women gave birth after a median of 39 weeks gestation [interquartile range (IQR)=38–40], 3 (9%) preterm births, 55% by caesarean section (82% obstetric reasons and 18% perianal fistulae). Of the 34 newborns, 53% were female, median birth weight was 3, 110 g (IQR=2, 820–3, 325), 3 (9%) low-birth weight, and 50% were breastfed exclusively. Median babies' follow-up was 12 months (IQR=7–16). During follow-up, 3 children (9%) had severe infections (2 urinary infections, and 1 bronchiolitis by respiratory syncytial virus). In addition, 4 (13%) children were hospitalized: 1 cardiorespiratory arrest, 1 prematurity, 1 jaundice, and 1 vesicoureteral reflux Conclusion: Ustekinumab seems to be safe during pregnancy in patients with IBD and their offspring.